'They Don't Want Foreigners': Zimbabwean migration and the rise of xenophobia in Botswana. Issue 2 (1st October 2015) - Campbell, Eugene; Crush, Jonathan
Xenophobia is becoming an increasingly common response to migration within the Global South, often taking the form of collective violence against migrants and refugees. It has also permeated central and local state structures leading to systemic discrimination, denial of basic rights and constant harassment of migrants and refugees. For a decade or more, South Africa has been plagued by xenophobic violence directed at Zimbabweans living in the country. Botswana is another major destination for Zimbabwean migrants but has not experienced violent attacks motivated by xenophobia. This does not mean that Zimbabweans are welcome in that country. On the contrary, xenophobic attitudes are highly prevalent amongst the citizenry and within government and manifested in a range of negative stereotypes. This article documents the rise of xenophobia in Botswana and provides empirical evidence from research with Zimbabwean migrants in Gaborone and Francistown of how xenophobia is actually experienced by its targets. In order to explain the existence of xenophobia in Botswana, usually considered one of Africa's most stable, economically prosperous and stable countries, the article draws on the literature on new nationalisms in Africa.